KINETICS OF DECOMPOSITION OF DOLOMITE FROM THE SHORSU DEPOSIT BY NITRIC ACID (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The kinetics was studied process of dolomite decomposition by nitric acid depending on concentration and temperature. The main kinetic parameters of the decomposition process are established and equations are derived for the dependence of the foam multiplicity constant on the acid feed rate.